Rhodopsins: An Excitingly Versatile Protein Species for Research, Development and Creative Engineering - de Grip, Willem J.; Ganapathy, Srividya (Frontiers in Chemistry, 2022)
The first member and eponym of the rhodopsin family was identified in the 1930s as the visual pigment of the rod photoreceptor cell in the animal retina. It turned out to be a membrane protein, owing its photosensitivity to the presence of a covalently bound chromophoric group. This group, derived from vitamin A, was appropriately dubbed retinal. In the 1970s a microbial counterpart of this species was discovered in an archaeon, being a membrane protein also harbouring retinal as a chromophore, and named bacteriorhodopsin. Since their discovery a photogenic panorama unfolded, where up to date new members and subspecies with a variety of light-driven functionality have been added to this family. The animal branch, meanwhile categorized as type II rhodopsins, turned out to form a large subclass in the superfamily of G-protein coupled receptors and are essential in multiple elements of light-dependent animal sensory physiology. The microbial branch, the type I rhodopsins, largely functions as light-driven ion pumps or channels, but also contains sensory-active and enzyme-sustaining subspecies. In this review we will follow the development of this exciting membrane protein panorama in a representative number of highlights and will present a prospect of their extraordinary future potential.